Factors Liable for Misinterpretation of Salivary Gland Neoplasms on Fine Needle Aspiration Cytology - Shah, Hijab; Haque, Anwar Ul (International Journal of Pathology, 2018)
Fine needle aspiration cytology (FNAC) is now considered an effective technique for evaluation of salivarygland tumors. However making precise diagnosis, at times, is a challenging job due to diversemorphological alterations and overlapping features of different tumors.Objective: 1) To determine different factors liable for misinterpretation of salivary gland tumors on fineneedle aspiration cytology. 2) To determine overall diagnostic accuracy of fine needle aspiration cytologyin salivary gland tumors using histopathology as gold standard.Design: Cross-sectional study. Setting: Department of Pathology, Pakistan Institute of Medical Sciences,Islamabad. Duration of study: From 15th October 2009 to 15th October 2010.Sample size: 51.Results: The sensitivity and specificity of FNAC came out to be 84.6% and 97.3% respectively with anoverall diagnostic accuracy of 98%. Out of 51 cases, 3 were wrongly diagnosed by FNAC. The majorfactors found responsible for this misinterpretation were; lack of standardization of cellular adequacyin salivary gland cytology smears, indeterminate exact criteria of definite atypia for malignancy andfailure to correctly identify different cell types.Conclusion: FNAC was found to be a useful diagnostic tool in the evaluation of salivary gland tumorsbecause of its simplicity, cost effectiveness, excellent patient compliance and high diagnostic accuracy.The diagnostic pitfalls in salivary gland FNAC, may be avoided by determination of definite predictiveatypical nuclear features and identifying non predictive, non relevant nuclear features. Repeat FNACwhen required and careful interpretation of slides could avoid and minimize mistakes. Support fromspecial stains may also be quite helpful.